Effects of DBT emotional regulation skills training program on depressive symptoms, anxiety symptoms and emotion regulation skills among Malaysian youth - Ching, Wai Yan (2023)
The aim of this study was to examine the effectiveness of a DBT emotion regulation skill training programme in developing emotional regulation abilities among Malaysian youth, based on the biosocial theory. Conducted as a single group quasi-experimental study, six participants aged 19-22 from different faculties in UTAR were recruited. The study utilized the Patient Health Questionnaire (PHQ-9), General Anxiety Disorder (GAD-7), and Difficulties in Emotion Regulation Scale (DERS-16) to measure variables. Pre- and post-tests were conducted by the researcher before and after the intervention. The results showed that the DBT emotion regulation skill training programme had a positive impact on depressive symptoms, with a clinically significant reduction. However, it had no effect on anxiety symptoms and emotion regulation skills. The study demonstrated that the programme's components and techniques, such as identifying and expressing emotions, fact-checking, using opposite actions to alter emotional responses, problem-solving skills, and ABC PLEASE techniques, can address issues leading to emotional dysregulation. These include unhealthy interpretations of incidents, misconceptions about emotions, unhealthy thought patterns, difficulty controlling impulsive behaviours during emotional states, inability to reduce the intensity of strong emotions, vulnerable physical, mental, and emotional states, feelings of helplessness and anxiety when dealing with emotions, and the inability to recognize one's own values. This study contributes to the field of study on DBT emotion regulation skill training programme's efficacy on a target sample of Malaysian youth with depressive issues and can serve as a reference for future studies with different research designs.